ChemInform Abstract: Copper‐Catalyzed N‐Cyanation of Sulfoximines by AIBN. Issue 28 (July 2015) - Teng, Fan; Yu, Jin‐Tao; Zhou, Zhou; Chu, Haoke; Cheng, Jiang
Abstract A simple and environmentally benign protocol for the direct cyanation of sulfoximines to N‐cyanosulfoximines is presented.